Gender Differences in Learning styles of Extension Trainees - P. Sethuraman Sivakumar; Ramesh C. Ray (Journal of Agricultural Extension Management, 2025)
Training is a crucial and continuous input for any efficient and effective transfer of technology system. Basically training aims to improve the efficiency in performing the tasks by imparting new knowledge and skills besides inculcating new attitudes in the behavioural system of the learners. In the era of liberalization, the concept of training has undergone a sea change with its focus shift from ’knowledge transfer’ to ’capacity building’. This approach demands a conscious effort from all the actors involved in the training process i.e. the trainer, trainee and sponsoring organization to plan and execute the learning exercise in the light of learner capacities and needs